Efecto in vitro de Pochonia chlamydosporia nativo sobre la viabilidad del estadio de huevo de Meloidogyne incognita - ARGOMEDO ALQUIZAR, Elizabeth Stephanie Nathalie (2019)
The in vitro effect of native Pochonia chlamydosporia on the viability of the egg stadium of Meloidogyne incognita was determinate. For this, two groups were used: a control group, which contained Meloidogyne incognita eggs and experimental group, which contained Meloidogyne incognita eggs with Pochonia chlamydosporia. From the Pochonia chlamydosporia pure cultures, a suspension of 2x106 conidia/mL in Potato Dextrose Broth and a suspension of 200 Meloidogyne incognita eggs/mL was prepared. To the experimental group, 0.5 mL of the suspension of 1x106 P. chlamydosporia conidia and 0.5 mL of suspension of 100 Meloidogyne incognita eggs was used, sowing by 5 points in Water Agar (2%). For the control group, only 0.5 mL of suspension of 100 Meloidogyne incognita eggs was used, sowing by 5 points in Water Agar (2%). Each group had six replicates, incubated for 96 hours and approximately 100 Meloidogyne incognita eggs in each plate was examined. These were evaluated as viable and non-viable eggs. It is concluded that native Pochonia chlamydosporia decreases the percentage of the egg stadium viability of Meloidogyne incognita in vitro.